Capacity of blood plasma is higher in birds breeding in radioactively contaminated areas - Ruiz-Rodríguez, Magdalena; Møller, Anders P.; Mousseau, Timothy A.; Soler, Juan J. (PloS one, 2017)
Environmental pollution in general, and radioactive contamination in particular, may deeply affect host-parasite relationships and their consequences for the evolution of organisms. The nuclear accident that occurred more than 30 years ago in Chernobyl resulted in significant changes in diversity and richness of microbial communities that could influence characteristics of animal-bacteria interactions, including host immune responses and competitive interference by bacteria. Given the high mortality rate of birds breeding in radioactively contaminated zones, those with stronger defences against infections should experience significant fitness advantages. Here we characterized antimicrobial capacity of barn swallows (Hirundo rustica) from different Ukrainian populations (subject to a gradient of ionizing radiation) against 12 bacterial species. We also quantified constitutive innate immunity, which is the non-specific first barrier of protection of hosts against microbial parasites. We found a positive association between specific antimicrobial capacity of individual hosts and radiation levels in breeding habitats even after controlling for other confounding variables such as sex and age. However, no significant relationship was found between immunocompetence (non-specific response) and background radiation. These results suggest that radiation selects for broad antimicrobial spectra of barn swallows, although not for all bacterial strains. We discuss these results in the framework of host-parasite evolution under extreme environmental conditions.